Beyond resource abundance: Evaluating the impact of mining and fiscal transfers on regional sustainable development index - Abae, Irawan; Ahmad, Abdul Chalid; Mala, Said (EcoProfit: Sustainable and Environment Business, 2025)
Background:  The mining sector in Indonesia has long been an important pillar of the country's economy. The region Sulawesi, Maluku and Papua is a region rich in resource nature such as minerals and energy, has contributed significantly to the national economy, especially through the export of mining products. However, along with the growth of the mining sector, various challenges have emerged, not only related to economic aspects, but also environmental and social impacts that threaten the sustainability of development. Natural resource curse theory : this theory states that countries or regions that depend on natural resources natural resources, such as mining, often experience slow economic growth or negative impacts. socio-environmental imbalance, so that its contribution to sustainable development become limited. Methods: Study This use two approach, First that is counting index sustainable development (IPB), and second, using the panel data regression method, covering 10 provinces in the Sulawesi, Maluku and Papua regions. Excluding the three new provinces in the Papua region, namely the Province South Papua, Central Papua, and Mountainous Papua. Findings: The results of the IPB calculations for each province in Sulawesi, Maluku and Papua regions using the development dimension. In general, the regions Papua and parts of Sulawesi showed high IPB achievements in 2024. However, there are disparities which is quite striking between provinces. The highest IPB figure is West Papua and the lowest is Maluku Province. Conclusion: Fiscal transfers of natural resources (SDA) and population have a significant influence. towards IPB, supported by theories and research that show the importance of resource management nature and population dynamics in sustainable development. As for the GRDP of the mining sector found to have no significant effect. The cause may be due to the impact of the natural resource curse and lack of practice mining sustainable. Matter this is what hinder his contribution to IPB. For to support sustainable development, better management of fiscal transfers of natural resources is needed, application of environmentally friendly technology in the mining sector, improving the quality of human resources and infrastructure to manage demographic pressures. Novelty/Originality of this article: This research provides novelty in terms of geographical context specifically in the regions of Sulawesi, Maluku, and Papua. Although This area is rich in natural resources, the implementation of sustainable development policies in this area still limited, especially due to infrastructure constraints, human resources, and differences in social conditions and culture.